Evaluation of the content of heavy metals in the waters of the Yamanigüey River - Dunán Avila, Pedro Luis (2021)
Heavy metals are among the most toxic environmental pollutants in recent times. The objective of this research was to evaluate the waters of the Yamanigüey River according to national and international standards for its use as drinking water, as this is one of the main rivers in the Moa region. Twelve samples were collected throughout the entire basin to evaluate the contents of aluminum (Al), chromium (Cr), hexavalent chromium (Cr+ 6), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn) and lead (Pb) using the atomic absorption spectrophotometry method. The results were contrasted with the corresponding norms of the WHO (2011) “Guidelines for the quality of water for human consumption”, with the Cuban Norm (2014) “Communal hygiene - sources of water supply - quality and sanitary protection and the Cuban Norm (2017) "Drinking water - sanitary requirements". The main results were that chromium, manganese, copper and zinc, in 100 % of the samples studied from the Yamanigüey River, according to the standards evaluated, are located below the maximum admissible limits (MAL).